Supramolecular Fluorescence Probe Based on Twisted Cucurbit[14]uril for Sensing Fungicide Flusilazole - Fan, Ying; Gao, Rui-Han; Huang, Ying; Bian, Bing; Tao, Zhu; Xiao, Xin (Frontiers in Chemistry, 2019)
The host-guest complex of the common dye, thioflavin T (ThT) and twisted cucurbit[14]uril (tQ[14]) was selected as a fluorescent probe to determine non-fluorescent triazole fungicides, including flusilazole, azaconazole, triadimefon, tebuconazole, tricyclazole, flutriafol, penconazole, and triadimenol isomer A, in an aqueous solution. The experimental results reveal that the ThT@tQ[14] probe selectively responded to flusilazole with significant fluorescence quenching and a detection limit of 1.27 × 10−8 mol/L. In addition, the response mechanism involves not only a cooperation interaction¾ThT occupies a side-cavity of the tQ[14] host and the triazole fungicide occupies another side-cavity of the tQ[14] host—but also a competition interaction in which both ThT and the triazole fungicide occupy the side-cavities of the tQ[14] host.